Self‐assembled liver organoids recapitulate hepatobiliary organogenesis in vitro. Issue 2 (2nd January 2018) - Vyas, Dipen; Baptista, Pedro M.; Brovold, Matthew; Moran, Emma; Gaston, Brandon; Booth, Chris; Samuel, Michael; Atala, Anthony; Soker, Shay
Abstract : Several three‐dimensional cell culture systems are currently available to create liver organoids. In gneral, these systems display better physiologic and metabolic aspects of intact liver tissue compared with two‐dimensional culture systems. However, none reliably mimic human liver development, including parallel formation of hepatocyte and cholangiocyte anatomical structures. Here, we show that human fetal liver progenitor cells self‐assembled inside acellular liver extracellular matrix scaffolds to form three‐dimensional liver organoids that recapitulated several aspects of hepatobiliary organogenesis and resulted in concomitant formation of progressively more differentiated hepatocytes and bile duct structures. The duct morphogenesis process was interrupted by inhibiting Notch signaling, in an attempt to create a liver developmental disease model with a similar phenotype to Alagille syndrome. Conclusion : In the current study, we created an in vitro model of human liver development and disease, physiology, and metabolism, supported by liver extracellular matrix substrata; we envision that it will be used in the future to study mechanisms of hepatic and biliary development and for disease modeling and drug screening. (Hepatology 2018;67:750‐761).